Impact of COVID-19 Lockdown on Various Stakeholders Associated with Dairy Food Supply Chain in Karnataka, India- An Evidence Based Study: Impact of COVID-19 on Dairy Food Supply Chain - G, GOVINDARAJ; M B, SHANABHOGA; H M, Swamy; M, Nagalingam; Shome, Bibek; Habibar, Rahman (Indian Journal of Dairy Science, 2022)
The present study assessed the disruptions in the dairy food supply chain and associated stakeholders due to COVID-19 in second-highest milk-producing state Karnataka, India. A cross-sectional survey using a multistage random sampling procedure was conducted and data was collected from the dairy food supply chain associated stakeholders in Karnataka, India. The results revealed that milk providers to the co-operatives increased by 4.67 % and the quantity of milk collection increased by 25.15 % during the lockdown. On the service front, 41.3% of the dairy cooperative societies faced animal feed shortages. The average per day milk consumption increased by 42.7 % during lockdown mainly driven by the return of family members from cities to villages. However, the gross income realized through milk sales by the dairy farmers decreased during the lockdown period mainly due to reduced milk prices offered by the co-operatives. The gross income realized through the sale of milk products by the vendors declined by 5.11% due to a fall in demand for various milk products. Despite many problems faced by the cooperative sector during the lockdown, it acted as a buffer and protected the dairy food supply chain from the free market and capitalist breakdown in Karnataka.